Bacteria bioburden assessment and MRSA colonization of workers and animals from a Portuguese swine production: a case report - Ribeiro, Edna (2018)
Pigs are an important reservoir of livestock-associated bacteria, including methicillin-resistant staphylococcus aureus (MRSA), which constitute a professional hazard for workers in direct contact with these animals with an increased risk of nasal colonization, potentially associated with subsequent clinical diseases and transference of the infection to others. Here we performed a bioburden characterization concerning bacterial prevalence and resistance (MRSA) in workers and animals from a Portuguese swine production as a case study. Air samples were collected through an impaction method. Biological samples were obtained through nasopharyngeal swab procedure. Identification of S. aureus was performed through immunologic tests. We report an exceedingly high prevalence of total bacteria and S.aureus colonization (100%) in workers and animals whereas all of the identified strains were MRSA. Additionally, air samples demonstrated high values of total bacterial concentration. This work raises awareness to the relevance of bioburden monitoring and the requirement to create occupational standards and take effective preventive measures.